2003
DOI: 10.1063/1.1596366
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of room-temperature microstructural evolution in copper films

Abstract: We studied the energetics and kinetics of microstructural evolution in copper films by estimating the magnitude of various possible driving forces for microstructural change that can be present in the as-deposited film. A driving force of at least 100 J/cm3 is required to account for the speed at which the grain boundaries move at room temperature. This value cannot be accounted for by only considering the minimization of grain-boundary energy and possible effects related to surface and strain energy as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 34 publications
4
48
1
Order By: Relevance
“…6, the activation energy for Cu recrystallization is 0.93 eV, which compares well to the activation energy obtained from isothermal data. Furthermore, this activation energy is similar to that of grain boundary selfdiffusion in Cu (0.92 eV) 15 and agrees well with the work of Detavernier et al 5 (0.92 eV) and Cabral et al 16 (0.92 ± 0.19 eV) on 970-nm-thick Cu films.…”
Section: Activation Energy For Recrystallizationsupporting
confidence: 90%
See 1 more Smart Citation
“…6, the activation energy for Cu recrystallization is 0.93 eV, which compares well to the activation energy obtained from isothermal data. Furthermore, this activation energy is similar to that of grain boundary selfdiffusion in Cu (0.92 eV) 15 and agrees well with the work of Detavernier et al 5 (0.92 eV) and Cabral et al 16 (0.92 ± 0.19 eV) on 970-nm-thick Cu films.…”
Section: Activation Energy For Recrystallizationsupporting
confidence: 90%
“…There was a debate in the literature regarding whether this phenomenon can be described as grain growth, abnormal grain growth, or recrystallization. 1,5 This debate stems from the fact that the grains grow at a rate higher than expected at room temperature, which suggests that the driving pressure for self-annealing is not dominated by grain-boundary area reduction. From transmission electron microscopy (TEM) observations, self-annealing was found to be driven by stored energy in the form of dislocations and can thus be described as recrystallization.…”
Section: Introductionmentioning
confidence: 97%
“…It is explained by the presence of lot of defects (grain boundaries, dislocations, stacking faults, etc.) [17]. In the case of such observation during Cu growth, grain boundary energy minimization may be the main driving force.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Rossnagel et al [103] and Bernat et al [104] showed that the resistivity in sputtered deposited copper films (with thickness below 100nm) descreases during storage after deposition. Detavernier et al observed self-annealing in sputtered deposited films up to 1500nm in thickness, and showed that the phenomenon is very dependent on the deposition parameters like the substrate temperature and sputter gas pressure and hence, on the microstructure of the as-deposited film [105][106]. In discussing the results, they used zone models to characterize the microstructure [107][108].…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%